2020
DOI: 10.1111/acv.12569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of species richness and detection between line transects, ground camera traps, and arboreal camera traps

Abstract: Monitoring trends in the occurrence of species over time is important for informing conservation plans and concurrent management actions. Understanding the effectiveness of field methodologies for collecting accurate and precise data is crucial for optimizing allocation of sampling effort and resources. In this study, we compared mammalian species richness and detection probabilities between three field methodologies: line transects, ground camera traps and arboreal camera traps in Nyungwe National Park, Rwand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 31 publications
3
44
1
Order By: Relevance
“…The number of arboreal mammals documented in this study is comparable to species richness reported in different arboreal camera trapping studies conducted in other tropical rainforest sites. In National Parks, Cameroon (Hongo et al, 2020), and 15 arboreal mammals at species level and 2 at genus level in Nyungwe National Park, Rwanda (Moore et al, 2020). Major differences to these studies, in relation to our study, relate to the high species richness of primates found in those habitats, and also squirrel species in Rwanda.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The number of arboreal mammals documented in this study is comparable to species richness reported in different arboreal camera trapping studies conducted in other tropical rainforest sites. In National Parks, Cameroon (Hongo et al, 2020), and 15 arboreal mammals at species level and 2 at genus level in Nyungwe National Park, Rwanda (Moore et al, 2020). Major differences to these studies, in relation to our study, relate to the high species richness of primates found in those habitats, and also squirrel species in Rwanda.…”
Section: Discussioncontrasting
confidence: 61%
“…To date, most of the studies reporting arboreal mammal assemblage in remnants of the Atlantic Forest have been based on ground-based surveys. Our findings demonstrate the potential of arboreal camera trapping to register rare, nocturnal and cryptic species that are prone to false negatives obtained by ground-based methods (Olson et al, 2012;Whitworth et al, 2016;Bowler et al, 2017;Moore et al, 2020). Considering the habits of some scansorial and terrestrial species, we suggest that arboreal camera traps should be paired with terrestrial cameras, which would reduce the likelihood of failing to detect these species.…”
Section: Discussionmentioning
confidence: 65%
“…At the same time, recent technological improvements in monitoring systems now enable the collection of a wide range of ecological data for terrestrial wildlife. For instance, camera traps have proved to be a useful, cost‐effective, and relatively low‐effort technique (Gregory et al ., 2014; Moore et al ., 2020). Furthermore, the development of automated radio‐tracking systems (Gottwald et al ., 2019) will likely allow us to determine the vertical movement patterns even of small animals (see Ripperger et al ., 2020) in the near future and thus will provide an increasingly detailed view of vertical movements of individual animals.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…2014; Moore et al . 2020), and to date, no studies have used arboreal camera trapping to monitor plant–frugivore networks over an extensive area.…”
Section: Figurementioning
confidence: 99%
“…However, arboreal camera trapping can operate remotely 24 hours a Plant-frugivore interactions revealed by arboreal camera trapping Camera trapping technology -which allows images of organisms to be obtained remotely from the field -has advanced rapidly in recent decades, and its infrared capability has become a standard tool in wildlife monitoring, especially for detecting ground-dwelling endothermic animals (O'Connell et al 2011). However, the activities of animals in arboreal habitats (including the forest canopy) are still poorly known (Gregory et al 2014;Moore et al 2020), and to date, no studies have used arboreal camera trapping to monitor plant-frugivore networks over an extensive area.…”
mentioning
confidence: 99%